Screening strategies for the detection of anal high-grade squamous intraepithelial lesions in women living with HIV. (1st December 2020) - Chiao, Elizabeth Y.; Lensing, Shelly Y.; Wiley, Dorothy J.; Deshmukh, Ashish A.; Lee, Jeannette; Darragh, Teresa M.; Einstein, Mark H.; Jay, Naomi; Berry-Lawhorn, John Michael; Palefsky, Joel M.; Wilkin, Timothy; Barroso, Luis F.; et al.
Abstract : Objective: HIV-infected women (WLHIV) have more than 10-fold higher risk for squamous cell cancer of the anus. Experts suggest cytology-based strategies developed for cervical cancer screening may prevent anal cancer by detecting anal cytologic or histological high-grade squamous intraepithelial lesion (hHSIL) for treatment. Currently, there is no consensus on anal-hHSIL screening strategies for WLHIV. Design: Between 2014 and 2016, 276 WLHIV were recruited at 12 US AIDS Malignancy Consortium clinical trials sites to evaluate hHSIL prevalence and (test) screening strategies. Methods: Participants completed detailed questionnaire, underwent anal assessments including high-risk human papillomavirus (hrHPV) testing using hrHPV-Hybrid Capture 2 (HC2) and hrHPV-APTIMA, anal cytology, and concurrent high-resolution anoscopy. Screening test characteristics for predicting hHSIL validated by central review of histologic diagnosis were estimated sensitivity, specificity, positive predictive value, and false-omission rate. Paired analyses compared sensitivity and specificity for hrHPV single tests to anal cytology alone. Results: 83% (229/276) of enrolled WLHIV had complete anal assessment data and were included in this analysis. Mean age was 50, 62% black and 60 (26%) had hHSIL. Anal cyotology (>atypical squamous cells of undetermined significance), hrHPV-HC2, and hrHPV-APTIMA sensitivity estimates were similarly high (83, 77, and 75%, respectively, P values > 0.2). Specificity was higher for both hrHPV-APTIMA and hrHPV-HC2 compared with anal cytology (67 vs. 50%, P  < 0.001) and (61 vs. 50%, P  = 0.020), respectively. Conclusion: Anal hrHPV testing demonstrated similar sensitivity for anal cytology (>atypical squamous cells of undetermined significance) to predict anal hHSIL. Among tests with similar sensitivity, the specificity was significantly higher for hrHPV-APTIMA and hrHPV-HC2. Thus, anal hrHPV testing may be an important alternative strategy to anal cytology for anal hHSIL screening among WLHIV. Abstract : Supplemental Digital Content is available in the text